Donor Cornea Harvest Techniques: Comparison Between Globe Enucleation and In Situ Corneoscleral Disc Excision. Issue 8 (August 2018) - Filev, Filip; Bigdon, Eileen; Steinhorst, Nils Alexander; Kammal, A.; Schröder, Carolin; Wulff, Birgit; Linke, Stephan; Feuerstacke, Jana; Hellwinkel, Olaf
Abstract : Purpose: To compare whole eye enucleation and corneoscleral disc (CD) excision as donor cornea harvesting techniques for possible effects on corneal cultivation and the clinical outcome of the corneal grafts after transplantation in 2929 cases. Methods: A retrospective analysis was performed on the Hamburg Eye Bank database using comparative statistics. The standard method for donor cornea recovery at the Hamburg Eye Bank changed from enucleation of the whole eye to CD in situ excision in 2008. Corneas recovered between 2003 and 2013 were included in this study. We compared the contamination rate, the endothelial density after retrieval, endothelial cell loss during cultivation, and the clinical outcome (visual acuity, astigmatism, and refraction) of transplanted corneas. Results: Once the retrieval method was changed from whole globe enucleation to in situ CD excision, the donation numbers increased (after several years of constant decrease). Furthermore, we observed slightly lower endothelial cell density after retrieval in corneas obtained by in situ CD excision compared with those from enucleated eyes, whereas endothelial cell loss during cultivation was similar. After changing the recovery procedure to in situ excision, initially a higher rate of contamination was observed, but but it eventually decreased. Finally, the corneas of both groups had a similar clinical outcome. Conclusions: After a transient technical learning period, in situ CD excision proved to be a method of donor cornea recovery with similar cultivation performance and clinical results compared with whole eye enucleation. It also may have led to higher willingness to donate, possibly because of better acceptance by the relatives of the deceased.